Endovascular Treatment of a Giant Renal Vein Aneurysm Arising from a High-Flow Arteriovenous Fistula. (January 2022) - Kalemci, Serdar; Kizilay, Fuat; Ergun, Kasim E.; Yurtseven, Emre; Cinar, Celal
Background: Renal vein aneurysms (RVAs) are considered rare clinical entities. RVAs can be secondary to thrombosis, venous hypertension, or renal arteriovenous fistula (RAVF). RVAs secondary to RAVF are rare. Patients with RVA may present with hypertension, abdominal pain, hematuria, or may even be asymptomatic. However, there may be life-threatening emergencies including aneurysm rupture, thrombosis, and pulmonary embolism. The treatment of RVAs includes reconstruction of the renal vein, nephrectomy, and endovascular treatment.Purpose: In this technical note, we report the endovascular treatment of a giant RVA that developed secondary to an acquired RAVF by the placement of multiple vascular plugs.Conclusion: Endovascular occlusion of the RAVF with vascular plugs is effective to prevent a life-threatening rupture of RVA. Clinical follow-up is crucial to detect leakage or migration of the vascular plugs.